Multi-factorial modulation of hemispheric specialization and plasticity for language in healthy and pathological conditions: A review. (January 2017) - Tzourio-Mazoyer, Nathalie; Perrone-Bertolotti, Marcela; Jobard, Gael; Mazoyer, Bernard; Baciu, Monica
Abstract: This review synthesizes anatomo-functional variability of language hemispheric representation and specialization (hemispheric specialization for language, HSL) as well as its modulation by several variables (demographic, anatomical, developmental, genetic, clinical, and psycholinguistic) in physiological and pathological conditions. The left hemisphere (LH) dominance for language, observed in approximately 90% of healthy individuals and in 70% of patients, is grounded by intra-hemispheric connections mediated by associative bundles such as the arcuate fasciculus and inter-hemispheric transcallosal connections mediated by the corpus callosum that connects homotopic regions of the left and right hemispheres (RH). In typical brains, inter-hemispheric inhibition, exerted from the LH to the RH, permits the LH to maintain language dominance. In pathological conditions, inter- and intra-hemispheric inhibition is decreased, inducing modifications on the degree of HSL and of language networks. HSL evaluation is classically performed in clinical practice with the Wada test and electro-cortical stimulation, gold standard methods. The advent of functional neuroimaging has allowed a more detailed assessment of the language networks and their lateralization, consistent with the results provided by the gold standard methods. In the first part, we describe anatomo-functional support for HSL in healthy conditions, its developmental course, its relationship with cognitive skills, and the various modulatory factors acting on HSL. The second section is devoted to the assessment of HSL in patients with focal and drug-resistant epilepsy (FDRE). FDRE is considered a neurological model associated with patterns of language plasticity, both before and after surgery: FDRE patients show significant modification of language networks induced by changes mediated by transcallosal connections (explaining inter-hemispheric patterns of language reorganization) or collateral connections (explaining intra-hemispheric patterns of language reorganization). Finally, we propose several predictive and explicative models of language organization and reorganization.